Scanning the Lawang Sewu for Eternal Historical 3D Documentation using Terrestrial Laser Scanner - Ilmawan, Hanif (Elipsoida : Jurnal Geodesi dan Geomatika, 2025)
Lawang Sewu is one of Indonesia’s iconic historical buildings, located in the city of Semarang. It currently serves as a museum and historical tourist attraction, holding significant historical and economic value. The preservation of such heritage structures requires meticulous documentation and structural integrity assessment. A crucial aspect of preservation is comprehensive 3D recording to ensure authenticity and conservation efforts. In this study, Terrestrial Laser Scanner (TLS) technology was employed to capture highly accurate data. The data acquisition process resulted in a detailed point cloud dataset representing the position, shape, color, and texture of all visible building surfaces. The 3D documentation obtained from this process serves as an important historical record of Lawang Sewu as of 2022. The accuracy of the 3D data was validated by comparing it to direct measurement data, yielding an RMSE value of 9.5 mm, indicating high accuracy.